Hydroxychloroquine in dermatology: New perspectives on an old drug. (15th October 2019) - Chew, Christopher Y; Mar, Adrian; Nikpour, Mandana; Saracino, Amanda M
Abstract: Hydroxychloroquine is an age‐old drug whose use as an immunomodulatory agent with a low side‐effect profile continues to expand. We present a review of this drug including recently updated prescribing recommendations and a summary of its clinical application in dermatology. A maximum daily dose of 5.0 mg/kg based on actual body weight and no greater than 400 mg is advised in order to reduce the risk of retinopathy, which is potentially permanent and has an estimated prevalence of 7.5% at 5 years on standard dosing. Baseline ophthalmologic assessment followed by annual screening after 5 years is recommended; however, closer monitoring should be considered in the setting of existing retinopathy, a cumulative dose > 1000 g or renal dysfunction. Hydroxychloroquine is now considered to be safe in pregnancy, and routine glucose‐6‐phosphate dehydrogenase (G6PD) deficiency testing is not required. Smoking can significantly decrease its efficacy although the reason is still uncertain. Hydroxychloroquine appears to also demonstrate antineoplastic and cardioprotective benefits.